Serum magnesium and calcium in preeclampsia: a comparative study at the Korle-Bu Teaching Hospital, Ghana - Owusu Darkwa E; Antwi-Boasiako C; Djagbletey R; Owoo C; Obed S; Sottie D (Dove Medical Press, 2017)
Ebenezer Owusu Darkwa,1 Charles Antwi-Boasiako,2 Robert Djagbletey,1 Christian Owoo,1 Samuel Obed,3,† Daniel Sottie4 1Department of Anaesthesia, University of Ghana School of Medicine and Dentistry, 2Department of Physiology, University of Ghana School of Biomedical and Allied Health Sciences, 3Department of Obstetrics and Gynaecology, University of Ghana School of Medicine and Dentistry, College of Health Sciences, 4Department of Anaesthesia, Korle-Bu Teaching Hospital, Accra, Ghana †Samuel Obed passed away on May 12, 2017 Background: A large percentage (16% of maternal mortality in developed countries, compared to 9% in developing countries), is due to hypertensive disorders in pregnancy. The etiology of preeclampsia remains unknown, with poorly understood pathophysiology. Magnesium and calcium play an important role in vascular smooth muscle function and therefore a possible role in the development of preeclampsia.Aim: We aimed to compare serum magnesium and total calcium levels of preeclamptic and normal pregnant women at the Korle-Bu Teaching Hospital in Ghana.Patients and methods: A comparative cross-sectional study involving 30 normal pregnant and 30 preeclamptic women with >30 weeks gestation and aged 18–35 years, was conducted at the Korle-Bu Teaching Hospital. Magnesium and calcium were determined using a flame atomic absorption spectrometer.Results: Mean serum magnesium and total calcium levels in preeclamptic women were 0.70±0.15 and 2.13±0.30 mmol/L, respectively. Mean serum magnesium and total calcium levels in normal pregnant women were 0.76±0.14 and 2.13±0.35 mmol/L, respectively. There was a statistically nonsignificant difference in serum magnesium and total calcium in preeclamptic women compared to normal pregnant women, with p-values of 0.092 and 0.972, respectively.Conclusion: Serum magnesium and total calcium, therefore, seem not to differ in preeclamptic women compared to normal pregnant women in Ghana. Keywords: electrolytes, maternal deaths, pregnant, hypertension, Ghanaian women